Numerical Analysis of Boring Bar Vibration Response in Internal Turning with Spherical Mass–Rubber Dynamic Vibration Absorber (MR-DVA) - Aufa Ulin Nuha; Wiwiek Hendrowati (Engineering Proceedings, 2025)
Vibration control in boring processes is essential to ensure machining accuracy and stability. This study analyzed the vibration response of a boring bar fitted with a combination of three pairs of spherical Mass–Rubber Dynamic Vibration Absorbers (MR-DVAs) with different stiffness constants during internal turning operations on a lathe machine. A customized boring bar with an internal cavity designed to house the spherical MR-DVA was employed. Modal analysis was performed using ANSYS software version 19.2 to determine natural frequencies, which were then applied in harmonic response simulations to analyze vibration behavior under an excitation force derived from cutting parameters including spindle speed, federate, and depth of cut. The dynamic response was evaluated in three axes (axial, tangential, and radial), highlighting the effectiveness of different rubber combinations. The results demonstrated that the integration of the spherical MR-DVA significantly reduced vibration amplitudes. These findings contribute to optimizing vibration control in deep-hole boring applications.